Quaternary stratigraphy of Panchkhal valley, Central Nepal - Timsina, Yadu Nath; Adhikary, Prakash Chandra (Bulletin of the Department of Geology, 2008)
The Panchkhal Valley is one of intermontane basins in the Central Nepal east of Kathmandu with two sets of neo-tectonic lineaments sited from satellite imagery and aerial photographs. One extending NNW-SSE east of the valley results the old Panchkhal Valley uplifting along south during Plio-Pleistocene age and second one NE-SW has ultimately uplifted the old valley. The Panchkhal Clay, Ratopairo Formation, Rampur Formation and Tamaghat Formation are four depositional lithostratigraphical units. Similarly, Tamaghat, Rampur, Thumka, and Chisapani surfaces are depositional and Basukidada, Sano-Tinghare, Sumara-Thulo Tinghare, Dhulikhel, Koiralathumka and Bhamarkot surfaces are erosional morphostratigraphic geomorphic surfaces. Geomorphic terrace cutting level is around 1400-1440 m and all surfaces and deposits above and below are relatively young.   doi: 10.3126/bdg.v10i0.1415 Bulletin of the Department of Geology, Tribhuvan University, Kathmandu, Nepal, Vol. 10, 2007, pp. 1-8